Lisa's assertion that Josh has played twelve times as many soccer matches as her is false. In actuality, Josh has played three times as many matches as Lisa.
Explanation:In the scenario, Lisa claims that her brother Josh has played in 12 times as many soccer matches as she has. To verify this statement, we would have to multipy the number of matches Lisa played by 12. Hence, 6 (Lisa's matches) times 12 equals to 72 matches. However, we know from the question that Josh has only played 18 matches. Therefore, Lisa's statement is incorrect because, in reality, Josh has only played three times as many matches as Lisa (18 divided by 6 equals 3), not 12 times as many.
Learn more about Multiplication and Division here:https://brainly.com/question/29354258
#SPJ12
Lisa's statement is not correct because Josh has played in 3 times as many soccer matches as Lisa.
Explanation:
Lisa's statement is not correct because she says Josh has played in 12 times as many matches as she has, but this is not the case. To determine how many times more matches Josh has played compared to Lisa, we can calculate the ratio of Josh's matches to Lisa's matches.
Josh has played in 18 soccer matches and Lisa has played in 6 soccer matches. To find out how many times more matches Josh has played, we divide Josh's matches by Lisa's matches:
Josh's matches / Lisa's matches = 18 / 6 = 3
So, Josh has played in 3 times as many soccer matches as Lisa. Lisa's correct statement would be that Josh has played in 3 times as many matches as she has.
The probable question can be: content loaded
Lisa has played in 6 soccer matches. Her brother Josh has played in 18 soccer matches. Lisa says Josh has played in 12 times as many matches as she has. Use the drop-down menus to explain why Lisa's statement is not correct. ( Click the arrows to choose an answer from each menu.
Lisa found the number that when _______. Instead, Lisa could have used the equation ________. Josh has played in _______ times as many soccer matches as Lisa.
what 1/8 of 12 in simplest form
Answer:
1½
Step-by-step explanation:
[tex] \frac{1}{8}(12) = \frac{12}{8} = 1 \frac{4}{8} = 1 \frac{1}{2} [/tex]
I am joyous to assist you anytime.
what are x- and y intercepts for the graph of 5x-2y=20 brainly.com
Answer:
(4, 0 ) and (0, - 10 )
Step-by-step explanation:
To find the x- intercept let y = 0 in the equation
5x - 0 = 20
5x = 20 ( divide both sides by 5 )
x = 4 ← x- intercept ⇒ (4, 0 )
To find the y- intercept let x = 0 in the equation
0 - 2y = 20
- 2y = 20 ( divide both sides by - 2 )
y = - 10 ← y- intercept ⇒ (0, - 10 )
The x- and y-intercepts of the equation 5x - 2y = 20 are 4 and -10 respectively. The x-intercept is obtained by setting y = 0, likewise, the y-intercept is obtained by setting x = 0.
Explanation:The x-intercept and y-intercept of an equation can be found by setting the other variable to zero and solving for the remaining variable. In the equation 5x - 2y = 20:
To find the x-intercept, we set y = 0, thus, the equation becomes 5x = 20. Solving for x, we get x = 4. To find the y-intercept, we set x = 0, so the equation becomes -2y = 20. Solving for y, we get y = -10.
So, the x-intercept is 4 and the y-intercept is -10 for the given equation.
Learn more about x- and y-intercepts here:https://brainly.com/question/32051056
#SPJ12
If Ed can paint the bedroom by himself in 3 hours, and his friend , Jake, works at the same pace as Ed does , how long will it take to paint the room if the boys work together?(shoe work)
Answer:
1.5
Step-by-step explanation:
1 person = 3 hours
2 people = 1.5 hours
Answer:
1 hour and 30 minutes
Step-by-step explanation:
Each one of them needs 3 hours to paint the bedroom,but now they are 2 people who work at the same place so together,they only need half of the time.
give that Tan^2 0=3/8 what is the value of sec0?
The value of sec(θ) given [tex]\tan^2(\theta) = \frac{3}{8}[/tex] is [tex]\frac{\sqrt{22}}{4}[/tex]. Using the identity [tex]\tan^2(\theta) + 1 = \sec^2(\theta)[/tex], we find [tex]\sec(\theta) = \frac{\sqrt{22}}{4}[/tex].
To find the value of sec(θ) given that [tex]\tan^2(\theta) = \frac{3}{8}[/tex], we'll use the trigonometric identity:
[tex]\[ \tan^2(\theta) + 1 = \sec^2(\theta) \][/tex]
Given that [tex]\(\tan^2(\theta) = \frac{3}{8}\)[/tex], we can plug this into the identity:
[tex]\[ \frac{3}{8} + 1 = \sec^2(\theta) \][/tex]
[tex]\[ \frac{3}{8} + \frac{8}{8} = \sec^2(\theta) \][/tex]
[tex]\[ \frac{11}{8} = \sec^2(\theta) \][/tex]
To find [tex]\(\sec(\theta)\)[/tex], we take the square root of both sides, but since sec(θ) is always positive, we'll take the positive square root:
[tex]\[ \sec(\theta) = \sqrt{\frac{11}{8}} \][/tex]
[tex]\[ \sec(\theta) = \sqrt{\frac{11}{8}} \times \frac{\sqrt{8}}{\sqrt{8}} \][/tex]
[tex]\[ \sec(\theta) = \sqrt{\frac{88}{64}} \][/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{88}}{\sqrt{64}} \][/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{88}}{8} \][/tex]
[tex]\[ \sec(\theta) = \frac{2\sqrt{22}}{8} \][/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{22}}{4} \][/tex]
So, the value of [tex]\(\sec(\theta)\)[/tex] given [tex]\(\tan^2(\theta) = \frac{3}{8}\)[/tex]is [tex]\(\frac{\sqrt{22}}{4}\)[/tex].
Complete Question:
Given that tan²(θ) = 3/8, what is the value of sec(θ)?
The value of sec(θ) given that tan²(θ) = 3/8 is (1/4)√22.
To find the value of sec(θ) given that tan²(θ) = 3/8, we first need to recall the relationship between tangent (tan) and secant (sec) functions.
The relationship is as follows:
[tex]\[ \tan^2(\theta) + 1 = \sec^2(\theta) \][/tex]
Given that [tex]\( \tan^2(\theta) = \frac{3}{8} \),[/tex] we can substitute this value into the equation above:
[tex]\[ \left(\frac{3}{8}\right) + 1 = \sec^2(\theta) \][/tex]
Now, let's simplify the expression:
[tex]\[ \frac{3}{8} + 1 = \frac{3}{8} + \frac{8}{8} = \frac{3 + 8}{8} = \frac{11}{8} \][/tex]
So, [tex]\( \sec^2(\theta) = \frac{11}{8} \).[/tex]
Now, to find the value of sec(θ), we take the square root of both sides:
[tex]\[ \sec(\theta) = \sqrt{\frac{11}{8}} \][/tex]
To rationalize the denominator, we multiply both the numerator and the denominator by [tex]\( \sqrt{8} \):[/tex]
[tex]\[ \sec(\theta) = \frac{\sqrt{11 \times 8}}{\sqrt{8 \times 8}} = \frac{\sqrt{88}}{8} \][/tex]
Now, we can simplify the expression under the square root:
[tex]\[ \sqrt{88} = \sqrt{4 \times 22} = 2 \sqrt{22} \][/tex]
So, the final expression for sec(θ) is:
[tex]\[ \sec(\theta) = \frac{2 \sqrt{22}}{8} \][/tex]
And if we simplify it further, we get:
[tex]\[ \sec(\theta) = \frac{\sqrt{22}}{4} \][/tex]
This is the final answer for the value of sec(θ) in terms of the given information.
The Complete Question:
Given that tan²(θ) = 3/8, what is the value of sec(θ)?
why can't 1.07 pounds of sugar be compared to 1.23 cups of sugar?
Answer:
A pound is a measure of weight and a cup is a measure of volume.
Step-by-step explanation:
You can't directly compare 1.07 pounds of sugar to 1.23 cups of sugar because they're measured in different units -- weight and volume -- and without a conversion factor (like density), they're not directly comparable. The solution is to convert one measurement to the other, such as by knowing that one cup of granulated sugar typically weighs about 0.44 pounds.
Explanation:The reason you can't directly compare 1.07 pounds of sugar to 1.23 cups of sugar is because they're measured in two different units -- weight and volume, respectively. Without a known conversion factor (in this case, the density of sugar), you can't equate the two. It's like comparing apples to oranges, the two quantities just aren't compatible without some more information.
Let's consider a real-world example. Just like you can't compare how heavy an object is to how much space it takes up without knowing the material's density, the same goes for comparing sugar in pounds and cups.
The solution is to convert one measurement to the other. For instance, by knowing that one cup of granulated sugar typically weighs about 200 grams (or 0.44 pounds), you could convert your weights and volumes to make a meaningful comparison.
Learn more about Converting Measurements here:https://brainly.com/question/34081145
#SPJ2
The axis of symmetry for a function in the form f(x) = x2 + 4x − 5 is x = −2. What are the coordinates of the vertex of the graph?
Answer:
The coordinates of the vertex of the graph are (-2, -9).
Step-by-step explanation:
The quadratic function is described by the standard equation The graph of a quadratic function is called a parabola.
We have the quadratic function
We identify the coefficients a, b, and c. For this equation,
The axis of symmetry is , i.e., Thus, the statement in the question for the symmetry axis x = -2 is correct.
The vertex (or turning point) is where or
The parabola opens upward because a > 0, resulting in a vertex that is a minimum.
Finding the minimum value is as follows:
Therefore, the coordinates of the vertex of the graph are (h, k), i.e.,
Other components:
The y-intercept of the quadratic function f(x) = x² + 4x - 5 is (0, c), i.e., the point
The factorization of f (x) = x² + 4x - 5 becomes f(x) = (x + 5)(x - 1). Then we get the x-intercepts at
Learn more
Which is the graph of f(x) = (x - 1)(x + 4) brainly.com/question/2334270
Finding the y-intercept of the quadratic function f(x) = (x – 6)(x – 2) brainly.com/question/1332667
The midpoint brainly.com/question/3269852
Keywords: the axis of symmetry, for a function, f(x) = x² + 4x − 5, x = −2, which is the graph of f(x) = (x - 1)(x + 4), what, the coordinates of the vertex of the graph, the x-intercept, quadratic function, a standard equation, the y-intercept, parabola, upward, the minimum value
Answer:
the vertex of the graph is (-2, -9)
Step-by-step explanation:
The given function is:
[tex]f(x)=x^2+4x-5[/tex]
Given x = -2 is the axis of symmetry and because we know that the vertex of the graph lies on its axis of symmetry
=> coordinate of vertex is (-2, y)
When x= -2 we have
[tex]f(-2) =(-2)^2+4(-2)-5\\<=> y=4-8-5\\<=> y=-9[/tex]
So the vertex of the graph is (-2,-9)
Complete the factorization of 4x2 – 9.
4x2-9= ( x-
x+ )
Answer:
1.) 2
2.) 3
3.) 2
4.) 3
Step-by-step explanation:
Fill in the blank to make the following statement true: 1,426 centigrams = _____ kilograms
A : 0.01426
B : 14.26
C : 1.426
D : 0.1426
Answer: A. 0.01426
Step-by-step explanation:
divide the mass value by 100000
Answer:
A. 0.01426
Step-by-step explanation:
divide by 10000
20 points if you answer right !!!!!HELP PLEASE
An experiment was conducted to test the following hypothesis it rains more in California then it doesn’t Arizona which of the following would show confirmation bias A.experiment suppose the hypothesis B.The scientist ignores Arizona desert because she doesn’t think it rains thereC.Experiment focuses equally on each states rainfall D. experiment prove a hypothesis to be true
Answer:
B
Step-by-step explanation:
When Experimenting scientist must include every part of the experiment and not leave out details.
Answer:b
Step-by-step explanation:
For which equation would x = 1 not be a solution?
x/1 = 1
x/2 = 2/4
x/3 = 3
x/4 = 1/4
Answer:
[tex] \frac{x}{3} = 3[/tex]
Step-by-step explanation:
[tex] \frac{1}{3} ≠ 3; \: \frac{9}{3} = 3[/tex]
I am joyous to assist you anytime.
Final answer:
The equation for which x = 1 is not a solution is x/3 = 3, as substituting x with 1 gives 1/3, which is not equal to 3.
Explanation:
To determine which equation x = 1 would not be a solution for, we need to substitute x with 1 in each equation and see if it holds true:
x/1 = 1: Substituting x with 1 gives us 1/1 = 1, which is true. Therefore, x = 1 is a solution.
x/2 = 2/4: Substituting x with 1 gives us 1/2 = 2/4, which simplifies to 1/2 = 1/2, also true. Hence, x = 1 is a solution.
x/3 = 3: Substituting x with 1 gives us 1/3 = 3, which is false, because 1/3 is not equal to 3. Therefore, x = 1 is not a solution here.
x/4 = 1/4: Substituting x with 1 gives us 1/4 = 1/4, which is true. Thus, x = 1 is a solution.
The equation for which x = 1 is not a solution is x/3 = 3.
Paul wants to gift wrap the boxes. He has 1,000.00 square inches of wrapping paper. Does Paul have enough to wrap all three boxes?
Answer:
y
Step-by-step explanation:
12 hundredths = how many tenths and hundredths
28.9-32.5
i will be fine i just forget the steps
Answer:
-3.6
Step-by-step explanation:
Since 32.5 is greater than 28.9, you just subtract 32.5 from 28.9 then add an equal sign. 32.5-28.9=3.6. With the negative, it would be -3.6
The value obtained by making the subtraction operation is -3.6
Subtracting ValuesTo perform the subtraction operation, the right hand side value is taken away from left hand side value .
Here , we have;
28.9 - 32.5 = -3.6We obtained a negative value because the right hand value is greater than the left hand value.
Learn more on numbers ::https://brainly.com/question/24997908
#SPJ3
Solve for x.
0 = 7x² + x + 5
a x=−1±i139‾‾‾‾√14
b x=−1±i105‾‾‾‾√14
c x=−1±i34‾‾‾√14
d x=−1±i120‾‾‾‾√14
Answer:
[tex]a \: \: x = \frac{ -1 ± i\sqrt{139}}{14} [/tex]
Explanation:
Since this is unfactorable, use the Quadratic Formula:
[tex]x = -b ± \frac{ \sqrt{ {b}^{2} - 4ac}}{2a} [/tex]
Now, take the information and input it:
[tex] -1 ± \frac{ \sqrt{1 - 4(7)(5)}}{2(7)} \\ \\ -1 ± \frac{ \sqrt{ -139}}{ 14} = \frac{-1 ± i\sqrt{139}}{14} [/tex]
I am joyous to assist you anytime.
Simplify the square root of 5 times the cube root of 5.
five to the five sixths power
five to the one sixth power
five to the two thirds power
five to the seven sixths power
Answer:
Option 3 - five to the two thirds power
Step-by-step explanation:
Given : Expression 'the square root of 5 times the cube root of 5'.
To find : Simplify the expression ?
Solution :
Writing expression in numeric form,
The cube root of 5 means [tex]\sqrt[3]{5}[/tex]
The square root of 5 times the cube root of 5 means [tex]\sqrt{5\sqrt[3]{5}}[/tex]
Now, simplify the expression
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{5\times (5)^{\frac{1}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{(5)^{1+\frac{1}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{(5)^{\frac{4}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=((5)^{\frac{4}{3}})^{\frac{1}{2}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=(5)^{\frac{4}{3}\times \frac{1}{2}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=(5)^{\frac{2}{3}}[/tex]
The expression is five to the two thirds power.
Therefore, Option 3 is correct.
The correct option is d. To simplify [tex]\(\sqrt{5} \cdot \sqrt[3]{5}\)[/tex], we get [tex]\(5^{5/6}\)[/tex]. Therefore, the correct answer is five to the seven sixths power.
To simplify [tex]\( \sqrt{5} \times \sqrt[3]{5} \)[/tex], we combine the radicals:
[tex]\[ \sqrt{5} \times \sqrt[3]{5} = 5^{1/2} \times 5^{1/3} \][/tex]
Using the property of exponents [tex]\( a^m \times a^n = a^{m+n} \)[/tex]:
[tex]\[ 5^{1/2} \times 5^{1/3} = 5^{1/2 + 1/3} \][/tex]
Now, find a common denominator for the exponents:
[tex]\[ \frac{1}{2} + \frac{1}{3} = \frac{3}{6} + \frac{2}{6} = \frac{5}{6} \][/tex]
Therefore,
[tex]\[ 5^{1/2} \times 5^{1/3} = 5^{5/6} \][/tex]
So, the simplified expression is [tex]\( {5^{5/6}} \).[/tex]
This corresponds to option (d) in your choices: five to the seven sixths power.
The complete question is- Simplify the square root of 5 times the cube root of 5.
a. five to the five sixths power
b. five to the one sixth power
c. five to the two thirds power
d. five to the seven sixths power
9. Find the missing value in the equation.
3/4- blank/3=5/12
Answer:
[tex]\large\boxed{\dfrac{3}{4}-\dfrac{1}{3}=\dfrac{5}{12}}[/tex]
Step-by-step explanation:
[tex]\dfrac{3}{4}-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}\\\\\bold{METHOD\ 1:}\\\\LCD=12\\\\\dfrac{3\cdot3}{4\cdot3}-\dfrac{4\cdot\boxed{\ }}{4\cdot3}=\dfrac{5}{12}\\\\\dfrac{9}{12}-\dfrac{4\boxed{\ }}{12}=\dfrac{5}{12}\\\\\dfrac{9-4\boxed{\ }}{12}=\dfrac{5}{12}\iff9-4\boxed{\ }=5\qquad\text{subtract 9 from both sides}\\\\-4\boxed{\ }=-4\qquad\text{divide both sides by (-4)}\\\\\boxed{\ }=1[/tex]
[tex]\bold{METHOD\ 2:}\\\\\dfrac{3}{4}-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}\qquad\text{subtract}\ \dfrac{3}{4}\ \text{from both sides}\\\\-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}-\dfrac{3}{4}\\\\-\dfrac{\boxed{\ }}{3}=\dfrac{5}{12}-\dfrac{3\cdot3}{4\cdot3}\\\\-\dfrac{\boxed{}}{3}=\dfrac{5}{12}-\dfrac{9}{12}\\\\-\dfrac{\boxed{\ }}{3}=-\dfrac{4}{12}\\\\-\dfrac{\boxed{\ }}{3}=-\dfrac{1}{3}\to\boxed{\ }=1[/tex]
The next number in the sequence -5, -2, 4, 13 is 25. Is this conjecture true or false?
Answer:
False
Step-by-step explanation:
The sequence seems to be increasing by 3+3(-5+3=-2, -2+3+3=4, so on). By 13, the sequence is increasing by 11, making the next number 24.
Answer:
the answer is true
Step-by-step explanation:
I just took the test and put false it was wrong
Simplify the following expression. 2^2 • 2^3
The simplification of the expressions give above would be = 32
How to simplify the given expression?To simplify the given expression the following steps needs to be taken as follows:
2²× 2³
Where;
2² = 2×2
2³ = 2×2×2
The simplification = 2×2×2×2×2= 32
Learn more about multiplication here:
https://brainly.com/question/29793687
#SPJ2
The first two steps in the derivation of the quadratic formula by completing the square are shown below.
Which answer choice shows the correct next step?
Step 1: ax^2+ bx+c = 0
Step 2: ax^2 + bx=-c
Answer:
The correct next step is the answer choice
[tex]x^{2} +\frac{b}{a}x=-\frac{c}{a}[/tex]
Step-by-step explanation:
we have the quadratic equation in standard form
[tex]ax^{2}+bx+c=0[/tex]
The steps in the derivation of the quadratic formula by completing the square are
step 1
[tex]ax^{2}+bx+c=0[/tex] ----> given equation
step 2
Move the constant term over to the right-hand side
[tex]ax^{2}+bx=-c[/tex]
step 3
The leading term is multiplied by a
so
Divide by a both sides
[tex]x^{2} +\frac{b}{a}x=-\frac{c}{a}[/tex]
step 4
Multiply the linear term by 1/2
[tex]\frac{b}{a}(\frac{1}{2})=+\frac{b}{2a}[/tex]
step 5
square this derived value
[tex]+\frac{b^2}{4a^2}[/tex]
step 6
Add this squared value to either side of the equation
[tex]x^{2} +\frac{b}{a}x+\frac{b^2}{4a^2}=-\frac{c}{a}+\frac{b^2}{4a^2}[/tex]
step 7
convert to the common denominator, and combine on the right-hand side
[tex]x^{2} +\frac{b}{a}x+\frac{b^2}{4a^2}=\frac{b^2-4ac}{4a^2}[/tex]
step 8
convert the left-hand side to completed-square form
[tex](x+\frac{b}{2a})^{2}=\frac{b^2-4ac}{4a^2}[/tex]
step 9
take the square roots of either side
[tex](x+\frac{b}{2a})=(+/-)\sqrt{\frac{b^2-4ac}{4a^2}} \\\\(x+\frac{b}{2a})=(+/-)\frac{\sqrt{b^2-4ac}}{2a}[/tex]
step 10
solving for the variable
[tex]x=-\frac{b}{2a}(+/-)\frac{\sqrt{b^2-4ac}}{2a}\\\\x=\frac{-b(+/-)\sqrt{b^2-4ac}}{2a}[/tex]
Answer:
C on edge
Step-by-step explanation:
Which of the following is a composite number?
A. 61
B. 111
C. 263
D. 307
can someone explain how to know if a number is composite and prime
Answer:
B.111
Step-by-step explanation:
111 is a composite number because the number can be divided evenly by more numbers than 1 and itself.
Jada says: “If you multiply a number by 0.001, the decimal point of the number moves three places to the left.” Do you agree with her statement? Explain your reasoning.
pls help
Step-by-step explanation:
Yes, I agree with her. If you multiply a number by .001 youll move the decimal point to the left 3 times. For example let's say 480. multiplied by .001. it will then become .480 or .48
Yes I agree I just did this in class
7(x+2)=2x-1 solve for the variable
Answer:
x = - 3
Step-by-step explanation:
Given
7(x + 2) = 2x - 1 ← distribute parenthesis on left side
7x + 14 = 2x - 1 ( subtract 2x from both sides )
5x + 14 = - 1 ( subtract 14 from both sides )
5x = - 15 ( divide both sides by 5 )
x = - 3
How do I do ( +7 ) - ( -2 ) = ?
Answer:
=9
Step-by-step explanation:
7−(−2)
=7−(−2)
=7+2
=9
Suppose the function h(t) gives the heart rate of a runner at various points in time, t, during a 10 mile run. Select an appropriate domain for this function. Assume that the runner completed the 10 mile run in 112 minutes.
Write the domain of this function using interval notation.
The domain of the heart rate function h(t) for a runner who completed a 10-mile run in 112 minutes is [0, 112] in interval notation.
Explanation:In this scenario, the domain of the function h(t) is the time duration during which the runner is running. Thus, since the runner completed the 10-mile run in 112 minutes, the domain is from 0 (the start of the run) to 112 (the end of the run). We represent this in interval notation as [0, 112]. The square brackets indicate that the endpoints are included in the domain. So, the domain of the function h(t) in this context is [0, 112].
Learn more about Domain of a function here:https://brainly.com/question/28599653
#SPJ3
Look at the following numbers:
-4, -1,0,4
Which pair of numbers has a sum of 0?
Answer:
-4 + 4
Step-by-step explanation:
because when you add a negative number with a positive number the sum will always equal 0
I am joyus to assist :)
Answer:
-4+4
Step-by-step explanation:
how to get 654 divided by 3 with partial quotients
Answer:
218 every part
Step-by-step explanation:
654/3 = 218
1/8 is called a terminating decimal
Explain
Answer:
Step-by-step explanation:
Maybe if we defined a non terminating fraction first, a terminating one would make more sense to you.
non terminating means that it goes on forever.
1/3 = 0.3333333333333333333333333333333....333333333333333333...333
I/3 never really ends.
1/8 on the other hand had
1/8 = 0.125 as a value and that's all there is. We're done.
So a terminating decimal ends.
What sequence of events explains why Anderson did not make any money from her patent?
Anderson was unable to capitalize on her invention, and other companies were able to profit from her invention without paying her.
The sequence of events that explains why Anderson did not make any money from her patent is as follows:
Anderson invented the windshield wiper in 1903.She patented her invention in 1905.She tried to sell her patent to a Canadian company, but they refused to buy it.She tried to sell her patent to other companies, but none of them were interested.Anderson did not have enough money to market and manufacture her invention herself.Other companies began to make and sell windshield wipers without her permission.Anderson could not afford to sue the companies for patent infringement.Anderson's patent expired in 1920.Anderson never made any money from her invention.The image of Mary Anderson and the First Windshield Wipers confirms this sequence of events. The image shows Anderson with a model of her windshield wiper invention. The text below the image states that Anderson "failed to sell her patent to any manufacturer" and that "her patent expired in 1920 without her making any money from her invention."
In addition to the information in the image, we can also infer that Anderson did not make any money from her patent because she did not have the business acumen or resources to bring her invention to market. She was a single woman with no business experience. She also did not have the financial resources to manufacture and market her invention on her own.
Radius of cone 15cm in height and 16cm in length
Final answer:
The curved surface area of a cone with a radius of 15 cm and a slant height of 16 cm is 753.982 cm², calculated using the formula A = πrl.
Explanation:
The question asks for the curved surface area of a cone with a given radius and slant height. To find the curved surface area of a cone, we use the formula:
A = πrl
where A is the area, π is pi (approximately 3.14159), r is the radius, and l is the slant height of the cone.
Here, the radius (r) is 15 cm and the slant height (l) is 16 cm. Substituting these values into the formula, we get:
A = π × 15 cm × 16 cm
A = 3.14159 × 15 cm × 16 cm
A = 753.982 cm²
Therefore, the curved surface area of the cone is 753.982 cm².
The circle graph shows how Lelia spends her day.
25%
School
10%
Homework
5% Soccer
40%
Sleeping
20%
Family Time
What percent of Lelia's day is spent on homework and school?
A 10%
B. 25%
C: 30%
D.35
E 40%
Answer:
D. 35%
Step-by-step explanation:
Note the percentage of each. You are trying to solve for the combination of homework and school.
In this case,
Homework = 10% of the pie chart.
School = 25% of the pie chart.
Add the two numbers together:
10 + 25 = 35
35% is your answer, or D).
~
Answer:
35%
Step-by-step explanation:
she spends 25% at or on school, and 10% on homework. all together (by adding) she spends 35%